Revisiting The Effect of Talent Management, Intrinsic Motivation, Job Satisfaction, and Affective Commitment on Employee Performance - Subagya, Subagya; Maharani, Anita; Hidayah, Zainur (Jurnal Manajemen, 2023)
This study aims to analyze the relationship between job satisfaction, affective commitment and intrinsic motivation in relation to talent management on employee performance. This study tries to elaborate on the talent management approach as a program carried out by organizations with individual motivation coming from the employees themselves in the form of job satisfaction, affective commitment and intrinsic motivation, where these two approaches have not been explored much in previous studies. The literature used in this study is related to these variables. This research method refers to the variance based structural equational modeling approach, this research was conducted at the Directorate General of Treasury, the respondents were employees at the head Office, regional offices and service Offices, which was carried out on 14 to 27 March 2022. The data obtained through 278 respondents will be processed using Smart PLS, and to make decisions regarding whether the hypothesis is proven or not, it will be reviewed from the P-values. The results showed that talent management did not affect performance, as well as affective commitment did not affect performance. Thus, it can be concluded from 7 hypotheses, which are proven as many as 5 hypotheses while 2 hypotheses are not proven which describe the phenomena that exist in the Directorate General of Treasury.